Microsleep And Occupational Safety: Integration Of Biometric Detection, Wearable Technology, And Preventive Policies For The Modern Industry - Ilhamsyah, Muhammad Helmy; Citra Budi, Savitri; Prihaswan, Irawadi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Microsleep is one of the factors that causes a decrease in vigilance that can have a serious impact on occupational safety, especially in industrial sectors with high risk levels such as heavy equipment and vehicle operations. This condition occurs suddenly and often escapes the detection of conventional surveillance systems, thus increasing the likelihood of work accidents. These challenges are even greater in a work environment with high operational burdens and rotating work patterns that affect the quality of sleep of workers. This study was conducted to evaluate the application of biometric-based detection technology and wearable devices combined with fatigue prevention policies. The study used a systematic literature review method on 25 primary articles published in the period 2020–2024 in a number of indexed international journals. The results of the analysis showed that the integration of real-time biometric monitoring with flexible work policies can increase the accuracy of microsleep detection by up to 85% and help reduce the potential for work accidents. This integrated approach is expected to be able to encourage the transformation of the occupational safety system to be more proactive, adaptive, and data-based, so as to create a safe and sustainable work environment.